MANAJEMEN PENGELOLAAN DANA ZAKAT: STUDI PADA PROGRAM BEASISWA CENDEKIA BAZNAS - Vika Marshanda (ISLAMISCHE BILDUNG: Jurnal Pendidikan Agama Islam, 2025)
Socio-economic factors such as poor family backgrounds are one of the obstacles tocontinuing a more decent education. However, with the Baznas Cendekia Scholarshipprogram organized by BAZNAS from the management of zakat funds, this is quite helpful inwhat are the special needs of the mustahik to improve their quality of life in the future so thatin the end they can escape the cycle of poverty and contribute back to society. The purpose ofthis study is to find out how zakat collectors, especially at the BAZNAS institution, managezakat funds and organize programs, one of which is in the field of education, namely theBaznas Cendekia Scholarship (BCB) program. This study uses a qualitative method with alibrary research approach. Data were collected from various written sources such as books,scientific journals, articles, research reports, and official documents that are relevant to thetopic of zakat, education, and scholarship programs for underprivileged families. The resultsof this study indicate that with the management of professional, transparent and accountablezakat funds, it has a very real impact on empowering the community, one of which is thatchildren from underprivileged family backgrounds can continue their education more decently. It has been proven that optimal management of zakat funds can be distributed to the right targets.